Review of the implementation of borne-by-government value added tax in the housing sector on the level of home ownership backlog in Indonesia - Fadhlurahman, Adam; Liyana, Nur Farida (WIM Solusi Prima, 2025)
The objective of this study is to examine the impact and influence of the Borne by Government Value-Added Tax (PPN-DTP) facility in the housing sector on the backlog rate of homeownership in Indonesia. Additionally, the research seeks to assess the effectiveness of this facility and its potential correlation with housing bubbles, as well as to provide relevant recommendations for future PPN-DTP policies in the housing sector. The study employs a mixed-methods approach, combining descriptive qualitative and quantitative methodologies. Primary data were collected through interviews with academics, officials from the Directorate General of Taxes, and taxpayers. Furthermore, the study utilized secondary data from public documents published by the Central Statistics Agency, the Ministry of Public Works and Housing, Bank Indonesia, and the Ministry of Finance of the Republic of Indonesia. The findings indicate that the PPN-DTP facility in the housing sector has a strong, positive, and significant impact and has proven effective in reducing the homeownership backlog in Indonesia. However, the sustainability of this facility in the long term requires further review, particularly regarding the eligibility criteria for beneficiaries and the urgency of strengthening oversight of the PPN-DTP facility by the Directorate General of Taxes to optimize its outcomes for the Indonesian public.